Ethnographic fieldwork a beginner's guide - Blommaert, Jan 1961-2021; Dong, Jie 1975- (Multilingual Matters, 2020)
Ethnographic fieldwork is something which is often presented as mysterious and inexplicable. How do we know certain things after having done fieldwork? Are we sure we know? And what exactly do we know? This book describes ethnographic fieldwork as the gradual accumulation of knowledge about something you don’t know much about. We start from ignorance and gradually move towards knowledge, on the basis of practices for which we have theoretical and methodological motivations. Jan Blommaert and Dong Jie draw on their own experiences as fieldworkers in explaining the complexities of ethnographic fieldwork as a knowledge trajectory. They do so in an easily accessible way that makes these complexities easier to understand and to handle before, during and after fieldwork. The 2nd edition of this bestselling book updates the 1st edition and includes a new postscript on ethnography in an online world
Keywords: digital ethnography; ethnography; online ethnography; research methods in linguistics; SOCIAL SCIENCE / Anthropology / Cultural & Social; Ethnology -- Fieldwork; Feldforschung; Ethnologie; Einführung